Experience of Malaysian Undergraduate Dental Students on the Appropriate Use of Systemic Antibiotics for Endodontic Pathology - Siti Hajar Omar; Jing Wei Choong; Jhia Shen Tan; Safura Anita Baharin (Univ. of Malaya, 2026)
Indexed by MyCite (Tier 3)